The psychology of social media - Mc Mahon, Ciarán (Psychology of everything., 2019)
Are we really being ourselves on social media? Can we benefit from connecting with people we barely know online? Why do some people overshare on social networking sites? The Psychology of Social Media explores how so much of our everyday lives is played out online, and how this can impact our identity, wellbeing and relationships. It looks at how our online profiles, connections, status updates and sharing of photographs can be a way to express ourselves and form connections, but also highlights the pitfalls of social media including privacy issues. From FOMO to fraping, and from subtweeting to selfies, The Psychology of Social Media shows how social media has developed a whole new world of communication, and for better or worse is likely to continue to be an essential part of how we understand our selves.